Defects in Hard Carbon: Where Are They Located and How Does the Location Affect Alkaline Metal Storage?. Issue 18 (18th March 2021) - Olsson, Emilia; Cottom, Jonathon; Cai, Qiong
Abstract: Hard carbon anodes have shown significant promise for next‐generation battery technologies. These nanoporous carbon materials are highly complex and vary in structure depending on synthesis method, precursors, and pyrolysis temperature. Structurally, hard carbons are shown to consist of disordered planar and curved motifs, which have a dramatic impact on anode performance. Here, the impact of position on defect formation energy is explored through density functional theory simulations, employing a mixed planar bulk and curved surface model. At defect sites close to the surface, a dramatic decrease ( ≥ 50%) in defect formation energy is observed for all defects except the nitrogen substitutional defect. These results confirm the experimentally observed enhanced defect concentration at surfaces. Previous studies have shown that defects have a marked impact on metal storage. This work explores the interplay between position and defect type for lithium, sodium, and potassium adsorption. Regardless of defect location, it is found that the energetic contributions to the metal adsorption energies are principally dictated by the defect type and carbon interlayer distance. Abstract : Oxygen, nitrogen, and carbon vacancy defects are known to be prevalent in hard carbons. The locations of these defects impact performance and are difficult to probe experimentally. Using density functional theory, it is shown that the defect location directly influences the defect concentration, with defect formation energy dramatically decreasing as the surface is approached.